Persistent VA dissociation during atrioventricular nodal reentry tachycardia: The existence of upper common pathway. Issue 6 (15th January 2019) - Iqbal, Mohammad; Munawar, Muhammad; Pramudya, Arsha; Karwiky, Giky; Achmad, Chaerul
Abstract: The existence of the upper common pathways is not well‐established yet. This case describes atrioventricular nodal reentry tachycardia with persistent ventriculoatrial dissociation that proof of upper common pathway existence.